Ayo Menabung di SDN Tambun Utara “Bersama-sama Memupuk Kebiasaan yang Baik untuk Masa Depan yang Lebih Baik” - Irsan, Maria Yus Trinity; Fitria, Risa (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
The program "Encouraging Savings for Children in Remote Elementary Schools" aims to improve students' financial literacy through an interactive and engaging approach. This program incorporates educational storytelling, saving simulations, and financial prioritization games tailored to the needs of students in remote areas. Evaluation results indicate an average improvement of 25% in students' financial understanding, with pre-test scores of 60% increasing to 85% in post-test assessments. Additionally, 70% of students have started practicing saving habits at home, supported by positive feedback from teachers and parents. Challenges such as limited time and inadequate facilities in some schools were key concerns. However, the effectiveness of interactive methods demonstrates the program's success in creating meaningful changes in students' understanding and behavior regarding financial management. With additional support, this program has the potential to be replicated in other regions, providing a broader impact on building financially aware and literate young generations